Left atrial enlargement and non-paroxysmal atrial fibrillation as risk factors for left atrial thrombus/spontaneous Echo contrast in patients with atrial fibrillation and low CHA2DS2-VASc score - Lin, Wei-Dong; Xue, Yu-Mei; Liu, Fang-Zhou; Fang, Xian-Hong; Zhan, Xian-Zhang; Liao, Hong-Tao; Tse, Gary; Wu, Shu-Lin (Journal of geriatric cardiology : JGC, 2020)
To determine the risk factors for thromboembolism in lower risk patients with non-valvular atrial fibrillation (AF) and low CHA2DS2-VASc scores, which remain undefined.OBJECTIVETo determine the risk factors for thromboembolism in lower risk patients with non-valvular atrial fibrillation (AF) and low CHA2DS2-VASc scores, which remain undefined.We retrospectively analyzed the baseline clinical characteristics, routine laboratory parameters, and echocardiographic measurements of 705 patients (71.1% male; mean age: 52.10 ± 9.64 years) with low CHA2DS2-VASc score (0 or 1; 1 point for female sex) out of 1346 consecutive patients with non-valvular AF who underwent transesophageal echocardiography (TEE) at Guangdong Cardiovascular Institute between January 2013 and December 2015.METHODSWe retrospectively analyzed the baseline clinical characteristics, routine laboratory parameters, and echocardiographic measurements of 705 patients (71.1% male; mean age: 52.10 ± 9.64 years) with low CHA2DS2-VASc score (0 or 1; 1 point for female sex) out of 1346 consecutive patients with non-valvular AF who underwent transesophageal echocardiography (TEE) at Guangdong Cardiovascular Institute between January 2013 and December 2015.Patients with left atrial thrombus (LAT) or spontaneous echo contrast (SEC) on TEE (24/705, 4%) showed a higher incidence rate of vascular disease (54.2% vs. 32.9%, P = 0.045) and non-paroxysmal AF (79.2% vs. 29.4%, P < 0.001), larger left atrial diameter (43.08 ± 4.59 vs. 36.02 ± 5.53 mm, P < 0.001), and lower left ventricular ejection fraction (58.23 ± 8.82% vs. 64.15 ± 7.14%, P < 0.001) than those without. Multivariate logistic regression analysis identified left atrial diameter [odds ratio (OR) = 1.171, 95% confidence interval (CI): 1.084-1.265, P < 0.001] and non-paroxysmal AF (OR = 3.766, 95% CI: 1.282-11.061, P = 0.016) as independent risk factors for LAT/SEC. In ROC curve analysis, a left atrial dimeter cutoff of 37.5 mm yielded 95.0% sensitivity and 62.7% specificity (AUC: 0.847, P < 0.0001, 95% CI: 0.793-0.914).RESULTSPatients with left atrial thrombus (LAT) or spontaneous echo contrast (SEC) on TEE (24/705, 4%) showed a higher incidence rate of vascular disease (54.2% vs. 32.9%, P = 0.045) and non-paroxysmal AF (79.2% vs. 29.4%, P < 0.001), larger left atrial diameter (43.08 ± 4.59 vs. 36.02 ± 5.53 mm, P < 0.001), and lower left ventricular ejection fraction (58.23 ± 8.82% vs. 64.15 ± 7.14%, P < 0.001) than those without. Multivariate logistic regression analysis identified left atrial diameter [odds ratio (OR) = 1.171, 95% confidence interval (CI): 1.084-1.265, P < 0.001] and non-paroxysmal AF (OR = 3.766, 95% CI: 1.282-11.061, P = 0.016) as independent risk factors for LAT/SEC. In ROC curve analysis, a left atrial dimeter cutoff of 37.5 mm yielded 95.0% sensitivity and 62.7% specificity (AUC: 0.847, P < 0.0001, 95% CI: 0.793-0.914).In patients with non-valvular AF with low CHA2DS2-VASc score, the presence of LAT or SEC was associated with left atrial enlargement, which had moderate predictive value, and non-paroxysmal AF.CONCLUSIONIn patients with non-valvular AF with low CHA2DS2-VASc score, the presence of LAT or SEC was associated with left atrial enlargement, which had moderate predictive value, and non-paroxysmal AF.